Design of new hole transport materials based on triphenylamine derivatives using different π-linkers for the application in perovskite solar cells. A theoretical study - Quezada-Borja, José David; Rodríguez-Valdez, Luz María; Palomares-Báez, Juan Pedro; Chávez-Rojo, Marco Antonio; Landeros-Martinez, Linda-Lucila; Martínez-Ceniceros, Mayra Cristina; Rojas-George, Gabriel; García-Montoya, Isui Abril; Sánchez-Bojorge, Nora Aydeé (Frontiers in Chemistry, 2022)
New organic molecules containing five different compounds, commonly called π-linkers, located between the triphenylamine units, were theoretically designed and analyzed in order to be proposed as new hole transport materials (HTMs) in perovskite solar cells, in total ten new molecules were analyzed. The electronic, optical and hole transport properties were determined, similarly, the relationship of these properties with their molecular structure was also investigated by Density Functional Theory (DFT) and Density Functional Tight Binding (DFTB) calculations. Eight of the ten analyzed compounds exhibited the main absorption band out of the visible region; therefore these compounds did not present an overlap with the absorption spectra of the typical methylammonium lead iodide (MAPI) hybrid-perovskite. The results showed that the HOMO levels of the compounds are higher than the perovskite HOMO level, and in some cases these are even higher than the Spiro-OMeTAD HOMO. The calculated electronic couplings and the reorganization energy values provided useful information in order to determine if the systems were hole or electron transport materials.